Histological study of the Vagus, Accessory and Hypoglossal nerves nuclei in one humped camel Camelus Dromedarius - Abass, T. A. (The Iraqi Journal of Veterinary Medicine, 2008)
The present work making histological studies of certain part of medullaoblongata on seven one humped camel ( Camelus Dromedarius ) of differentages and sexes. The location of Vagus X, accessory XI and hypoglossal XIInerve nuclei. The hypoglossal nerve XII nucleus consist of two nuclei dorsalgreater and ventral smaller and the dorsal nuclei observed. Connected withdorsal motor vagal nucleus X by specific arch of fiber in many sections andanother observation the root fiber of hypoglossal nucleus XII pass along thelateral border of inferior olivary nucleus and some sections the root fiberpenetrate lateral part of inferior olivary nucleus.